Tinjauan Hukum Islam Terhadap Jasa Endorser di Media Sosial - Muhammad Irkham Firdaus (Fakultas Syari'ah Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo., 2022)
In the marketing strategy, Endorsement is one of the strategies of business actors to introduce goods or service products to consumers through the intermediary of actresses, youtubers, or selebrgram, especially on Instagram or youtube social media. And celebrities have accounts on social media, especially Instagram and their youtobe accounts have many followers, and make an impact on many parties seeing the uploads of these actresses, youtobers and selebgrams. In this transaction using a service rental system that is paid and has a grace period. The freedom of business actors in using endorsement services has many impacts, both positive and negative impacts. This shows that the endorsement strategy is an ijarah contract that uses a written contract in terms of freedom, the endorsement strategy has several negatve impacts. And this endorsement strategy includes 3 parties, namely business actors who use endorsement services, actresses, youtubers and celebrities who receive endorsement services, and finally consumers who buy the products after seeing products that have been introduced through endorsement services. But there are also many endorsements of goods or services that are not in accordance with the shari’a which can damage the ijarah contract, and cause the contract to be invalid or defective because it does not meet the requirements and pillars of ijarah conract. Then, discrepancies were found regarding buying and selling between business actors and consumers, resulting in fraud gue to online transaction that cannot meet face to face and it is difficult to know whether these business actors are truly trustworthy or can harm consumers. Then regarding Islamic business ethics between actresses, youtobers, and celebrities against brand account followers who become consumers for business actors on social media, several discrepancies were also found regarding the concept of Islamic business ethics and the principles of Islamic business ethics